2014
DOI: 10.1021/jp5087448
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Allotropes Accelerate Hydrogenation via Spillover Mechanism

Abstract: Solid-phase hydrogenation kinetics can be substantially increased by utilizing hydrogen spillover phenomenon. Carbonaceous allotropes are considered as promising spillover agents (SOAs) for improved hydrogen transport rate. We studied the effect of carbon-based SOA properties on irreversible hydrogenation. We divided the reaction into two major stages, near-and far-field hydrogenation (with respect to a catalyst), and determined their rate-limiting steps. The hydrogenation kinetics was analyzed for hydrogen or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…3941 The UV-vis spectrum of PdNP/GO hybrids shown in Fig S3 (a) was consistent with the spectra of other palladium nanoparticles with similar core sizes, which showed no absorption or plasmon bands with only an exponential decay with increasing wavelength from 300 nm to 800 nm. 19 IR spectrum of PdNP/GO shown in Fig S3 (b) showed a C=O stretch at 1725 cm −1 , sp 3 C-H stretch at 2938 – 2878 cm −1 and a broad O-H stretch at 3300 – 2800 cm −1 , corresponding to the IR characteristics of ω-carboxylate-1-hexanethiolate ligands and GO.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…3941 The UV-vis spectrum of PdNP/GO hybrids shown in Fig S3 (a) was consistent with the spectra of other palladium nanoparticles with similar core sizes, which showed no absorption or plasmon bands with only an exponential decay with increasing wavelength from 300 nm to 800 nm. 19 IR spectrum of PdNP/GO shown in Fig S3 (b) showed a C=O stretch at 1725 cm −1 , sp 3 C-H stretch at 2938 – 2878 cm −1 and a broad O-H stretch at 3300 – 2800 cm −1 , corresponding to the IR characteristics of ω-carboxylate-1-hexanethiolate ligands and GO.…”
Section: Resultssupporting
confidence: 76%
“…The increase in the kinetics of substrate delivery by the spill-over, that has been observed by others for catalysts on graphene substrates, was absent for the colloidal PdNP/GO catalysis. 40,41 For PdNP catalysts, most DMAD was hydrogenated to maleic ester, the semi-hydrogenated product in a cis-form (>99% selectivity), in less than 3 h reaction time. However, the initial rate of reaction using PdNP/GO catalysts was slightly slower despite that the reaction resulted in the products with similar selectivity (shown in Table S2, which summarizes the turn-over-frequency (TOF) for semi- and full-hydrogenation products in the hydrogenation of DMAD).…”
Section: Resultsmentioning
confidence: 99%
“…In line with this argument, Pevzner et al [19] found the addition of carbon nanotubes (CNT) to a Pd/C catalyst benefiting the hydrogenation reaction even when the reactants and catalyst were contacted in the solid phase. The same group observed the hydrogenation rate decreased as CNT > graphene > activated carbon, and mentioned that on CNT hydrogen spillover is faster [20]. This result is supported by an observation that the curvature of carbon materials has a pronounced effect on mobility of H atoms [17].…”
Section: Introductionmentioning
confidence: 77%
“…This concept was developed fully and gained application in the field of hydrogen storage. Pevzner et al . studied solid‐phase hydrogenation kinetics on different carbonaceous allotrope spillover agents and found a dimensionality effect of the support on the hydrogen transport rate.…”
Section: Introductionmentioning
confidence: 98%